Molar Incisor Hypomineralization: Optimizing Treatment Protocols for Hypersensitivity: A Randomized Clinical Trial - Elena Bardellini; Francesca Amadori; Laura Rosselli; Maria Luisa Garo; Alessandra Majorana; Giulio Conti (MDPI AG, 2024)
Dentin hypersensitivity (DH) is a common challenge in pediatric patients with molar incisor hypomineralization (MIH), stemming from enamel porosity or exposed dentin after enamel breakdown. This three-arm randomized controlled clinical trial aims to evaluate the effectiveness of three different desensitizing treatment protocols. The study was conducted on 39 children, aged 6-14 years old, with MIH and DH. Group A received casein phosphopeptide plus amorphous calcium phosphate fluoride (CPP-ACPF) mousse and sham light therapy, Group B received placebo mousse and photo-bio-modulation therapy (PMBT), and Group C received both CPP-ACPF mousse and PMBT. DH evaluation using a visual analogue scale was performed at multiple time points. Both CPP-ACPF mousse and PMBT individually demonstrated desensitizing effects on dental elements affected by MIH. While PMBT had a greater immediate effect, the combination of the two therapies proved most effective in reducing DH. The VAS scores were statistically lower in group C compared to groups A and B, both after the first session (p = 0.0001) and after 28 days (p = 0.0005). This study suggests promising avenues for managing DH in MIH patients, highlighting the potential of combined therapies, specifically CPP-ACPF mousse and PMBT, for enhanced clinical outcomes.